Opinions, perceptions and practice of gynecologists and obstetricians in regar ds to reporting pati ents with induced abortion to the Police, Lima, Peru, 2014 - Sánchez Calderon, Sixto (2015)
Problem: Practice of reporting cases of women with induced abortion to the police is relatively common and add legal and police problems to these patients. Objective: To determine perception, opinion, knowledge, attitudes and practices of gynecologists regarding information given to the police on patients with induced abortion. Design: Qualitative participatory, and quantitative observational cross-sectional prospective study. Setting: Three hospitals of the Ministry of Health (MINSA), Lima, Peru. Participants: Gynecologists and obstetricians. Methodology: Thirty-three obstetricians and gynecologists from three hospitals were systematically selected for in depth interview. Other 69 doctors completed a standardized self-administered questionnaire. Participation was voluntary and the study was reviewed and approved by the ethics committee of each of the three hospitals. Main outcome measures: Information to the police on cases of induced abortion. Results: 78.3% of participants knew there is a law requiring the report of cases of induced abortion to the police, 43.5% disagreed with this rule, and 58% agreed with the right of professional secrecy. However, 43.5% of participants reported to the police the last induced abortion attended. The main reason was to comply with the law as well as fear to be identified as an accomplice and the criminal consequences. Conclusions: The practice of reporting women with induced abortion confronts confidentiality of the medical act. Recommendations: Modification or abolishment of Article 30 of the Peruvian Health General Law is proposed. Instead a coordinated and coherent national program of responsible parenthood, contraception and family planning should be implemented.